A Case with Musculocutaneous Nerve Not Perforating the Coracobrachialis Muscle and Giving A Communicating Branch to Median Nerve - Esen, Gülru; Şakul, B. Ufuk (Fırat University, 2001)
Objective: Anatomical variations are very important for preventig surgical complications. The nervous variations are rarer than vascular variations. We decide to publish the variation that we encountered. Material: During routine cadaver dissection, in the labratory of Faculty of Dentistry of Ankara University, we encountered a variation in a sixty years old female cadaver. The variation was on the right side. In this variation, musculocutaneous nerve didn't pierce the corachobrachialis muscle and there was a communicating branch running from the musculocutaneus to median nerve. The communication is in the middle of the arm. Conclusion: It's possible that combined paralysis of the musculocutaneous and median nerves would occure. The present variation may be important to clinicians. If the surgeon finds it necessary to isolate and trace the median or/and musculocutaneous nerve, he or she must be very sensitive to communications that may occure between them.

Amaç: Anatomik varyasyonların ve karşılaşılma sıklıklarının bilinmesi, bölgenin cerrahi girişimleri sırasında meydana gelebilecek komplikasyonları önlemede önemlidir. Varyasyonların en az görüldüğü yapı sinirlerdir. Bu amaçla, rutin diseksiyon sırasında karşılaştığımız bu sinir varyasyonunu yayınlamayı uygun gördük. Materyal: Ankara Üniversitesi Diş Hekimliği Fakültesi'nde öğrenci eğitimi için kullanılan 60 yaşındaki bir kadın kadavra. Bulgular: Anatomi laboratuvarında yapılan rutin diseksiyon islemi sırasında 60 yaşındaki bir kadın kadavranın sağ üst ekstremitesinde n. musculocutaneus'un m. Coracobrachialis'i delmediği ve kolun ortalarında n. medianus'a birleştirici bir dal verdiği gözlendi. Sonuç: İki sinir arasındaki birleşmenin bilinmesi, omuz eklemi travmaları ve operasyonlarında kıymetli bir bilgi olma özelliğindedir. bu varyasyon iki sinirin kombine paralizlerine neden olabilmesi bakımından klinikte çok önem taşımaktadır.
MUSCULUS CORACOBRACHİALİS'İ DELMEYEN VE NERVUS MEDİANUS'A BİRLEŞTİRİCİ DAL VEREN BİR NERVUS MUSCULOCUTANEUS OLGUSU